Siesmic Stratigraphy of Upper Pleistocene gravel and holocene mudbelt deposits between wreck point and the kamma river on the western shelf of South Africa - Lodewyks, Therisia (Department of Geological Sciences, 2014)
This project aims to provide a better understanding of the deposition of Quaternary and Holocene sediments along the west coast of Southern Africa between Wreck Point at approximately 28º50.00′S and the Kamma River at approximately 29º20.00′S, based primarily on seismic stratigraphy. The high resolution airgun seismic survey performed by De Beers Marine during 1998 was interpreted based on seismic stratigraphic principles and the chronology of the seismic profiles was based on correlation to radiocarbon-dated gravity cores from offshore the Holgat River determined by Herbert (2009). Seismic profiles were interpreted to the north and south of the central Holgat River sequence with the identified Type 1 Sequence divided into systems tracts. The Type 1 Sequence Boundary represents a major erosional unconformity formed as a result of tectonic uplift and a relative drop in sea level. A wave-cut knick point provides accommodation space for the deposition of Pleistocene and Holocene sediment above the erosional unconformity. The Lowstand Systems Tract (LST) consists of a condensed gravel lag. The LST is divided into subunits where possible which reflect the complex depositional history as the gravel lag was variably reworked as the strandline migrated across the shelf in response to late Pleistocene sea-level fluctuations. This study attempts to delineate some of the more distinctly different units within the economically important gravel body of the LST. The extent and seismic character of five subunits were identified within the complex LST. The Transgressive Systems Tract (TST) formed after a rapid rise in sea level between 19 and 7 thousand years ago (ka). Two transgressive packages were formed as sea level migrated landward. An older deeper water package was identified and labelled Unit 4 while a younger shallower water package was identified upslope, Unit 5, as the mudbelt depocentre migrated landward. The Highstand Systems Tract (HST) is characterized by a set of prograding sigmoidal clinoforms having formed in response to increasingly limited accommodation space after 5.5 ka. Clinoforms, seismic reflectors with slightly higher amplitude than the underlying units, represent depositional hiatuses during periods of lower sedimentation rates. The HST units show southward progradation as accommodation space around the Orange River Mouth became limited. The resulting sequence startigraphy and stratal geometries of the studied sequence are controlled by sea level fluctuation, accommodation space and sediment supply.